Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content1. Realizing an innovative design vision for clothes suitable for girls with visual impairmentsDr. Roua Suhail Qadi2. Information sources for the virtual audience about the Uyghur crisis and its impact on public opinion regarding China's policy are analyzed through An analytical study of the Arabic China News page on TwitterDr. Hussein Abdalla Saad3. Studying some variables related to social capital of rural people in some villages of Kafr El-Sheikh Governorate – EgyptDr. Walaa Abdelatif Shabaan , Dr. Dalia Hassan Hebish, Dr. Amany Said Elkholy4. Social Responsibility and The Development of The Human Element: A Descriptive Study on A Sample of Beneficiaries of Social Responsibility Programs at The Royal Commission in YanbuMr. Suhayb Mousa Abu Shurayyan5. The social and economic cost of divorce from the perspectives of employees at social development committees in Riyadh CityMr. Mamdouh Abdalla Elheky 6. Analysis of the tools and materials used in tailoring, embroidering and weaving the Bisht, the stages of embroidering the Bisht, its names and coloursCo-Prof. Khyrah Awad Awadh Alzahrani7. Factors leading to the quality of family life and their relationship to resilience in the Corona crisis in Jeddah GovernorateMrs. Hana Ali Aali Al-Malki8. Self-Efficacy Beliefs of Yemeni Graduate Students about themselves as Competent ResearchersProf. Mohammad Abdu Ahmed Al-Mekhlafi , Dr. Osamah Mohammed Abdu Al-Mekhlafi
Keywords: Journal of Human and Social Sciences